Room temperature crystal structure and high temperature structural and magnetic phase transitions in Sr(Fe0.5Nb0.5)O3 ceramic - Kumar S.; Singh A.K. (My University, 2025)
The room temperature structure of the perovskite Sr(Fe0.5Nb0.5)O3 ceramic has been investigated by Rietveld structure refinement using high resolution X-ray diffraction (XRD) data. The correct structure is determined to be tetragonal in the space group I4/mcm ruling out orthorhombic (Pbnm), tetragonal (P4 mm), and monoclinic structures previously reported by authors. The high temperature structural phase transition has been studied by Rietveld analysis using the high resolution XRD data in the temperature range of 300-850 K. A high temperature structural phase transition is observed from tetragonal (I4/mcm) to cubic (Pm3m) phase around ∼630 K. This phase transition was also confirmed by the heat flow experiment using differential scanning calorimetry. To confirm the nature of phase transition, we have studied the variation of integrated intensity (ISL) of superlattice peak and the oxygen octahedral tilt angle (φ) in a tetragonal structure with temperature. The temperature variations of these two parameters provide evidence for the tricritical nature of the phase transition. A magnetic phase transition is discovered in temperature dependence of magnetization M(T) around ∼708 K, which coincides with the dielectric anomaly temperature in loss tangent. © 2019 Author(s).